Association of School‐Based Influenza Vaccination Clinics and School Absenteeism—Arkansas, 2012‐2013. (April 2016) - Gicquelais, Rachel E.; Safi, Haytham; Butler, Sandra; Smith, Nathaniel; Haselow, Dirk T.
ABSTRACT: BACKGROUND: Influenza is a major cause of seasonal viral respiratory illness among school‐aged children. Accordingly, the Arkansas Department of Health (ADH) coordinates >800 school‐based influenza immunization clinics before each influenza season. We quantified the relationship between student influenza vaccination in Arkansas public schools and school absenteeism during the 2012‐2013 influenza season. METHODS: The relationship between the percent of students vaccinated in Arkansas public schools during ADH‐facilitated clinics and the average daily percent of students absent from school during the 2012‐2013 influenza season was quantified using linear regression modeling. The effect of increasing vaccination coverage among students on absentee days in the Arkansas public school system was estimated. RESULTS: For every 1% higher vaccination coverage, 0.027% fewer absenteeism days were predicted. Larger school size was associated with higher absenteeism and predicted decreases in absenteeism were larger in magnitude for larger schools compared with smaller schools. Extrapolation of the model showed that a 10% higher vaccination level was associated with a reduction of 16‐163 student absentee days per school over a 12‐week influenza season. CONCLUSIONS: Influenza vaccination is an effective tool to reduce school absenteeism. School‐based clinics are a feasible way to target influenza vaccinations to school‐aged children.